Curriculum for pharmacology in pharmacy institutions in India: Opportunities and challenges - Goyal, Ramesh K. (Medknow Publications & Media Pvt Ltd, 2014)
The curriculum of pharmacy institutions in India is regulated by the All India Council for Technical Education (AICTE) and the Pharmacy Council of India (PCI) at degree and diploma levels. However, it has been over two decades that the syllabi have been revised by these regulatory agencies. Considering the dynamic character of pharmacology, it is essential to prepare a syllabus that caters to the contemporary needs of the academic institutions and pharmaceutical industry, the community. Pharmacists are also witnessing a greater role in community pharmacy practice as well as in several healthcare sectors. Considering these facts, a panel discussion was held at IPSCON 2013, (the Annual Conference of Indian Pharmacological Society) at Bangalore. The discussion saw several recommendations for syllabi for institutions offering various pharmacy courses to meet the objectives of teaching, learning and research in Pharmacology. This article documents a summary of the discussion. For B. Pharm. course, a balance between industry-oriented pharmacology and clinical pharmacy has been recommended. Redundant animal experiments should be replaced with the simulation experiments or those which are feasible in the light of stringent regulations of the Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA). It is recommended that the M. Pharm curriculum should focus on preclinical research with the inclusion of molecular biology and experiments on gene expression, proteomics, pharmacogenomics, cell culture and tissue culture. In general, at all levels, exposure of students to hospitals and clinicians is needed. Pharm. D., syllabus too should lay lesser emphasis on experimental pharmacology. Present experiments in the D. Pharm. course have no relevance to the program objectives and hence, only experiments through demonstrations or simulated preparations or interactive videos maybe undertaken. Regulatory bodies as well as universities should design a comprehensive syllabus and plan an effective pedagogy to prepare graduates who are competent and capable of bringing positive changes in the community and healthcare in India.